Boys will be boys and girls will be good the gender ideologies reflected in selected stories for Filipino hildren - Luna, Monalyn L.; Ruiz, Yvette Christina P.; Yanilla-Aquino, Lalaine F. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2009)
This study analyzes eight short stories for children focusing on what gender ideologies are reflected in them and how these gender ideologies are represented through the clause structures of the stories. The study made use of Halliday's Transitivity system to find out how realities are constructed through language. Sara Mills' Feminist Stylistics, along with other Gender theories, was also used in interpreting the results of the analysis of the transitivity processes found in the language of stories. Four of the short stories are realistic and the other four are fantastic. Two female authors and two male authors were chosen. Then two stories per author were chosen. The fantastic stories were written by the male writers, while the realistic stories were written by the female characters. The results were compared and contrasted based on the gender of the author and the subgenre of the stories. The study found out that most gender ideologies are traditional and still follow most of the stereotypical views of society. These include female's being nurturing, caring, and other-oriented, and self-conscious when it comes to appearance. Males are often portrayed as active, authoritative, and strong. These are true for both subgenres and for both genders of authors.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.